A Joint Evaluation of Neurohormone Vasopressin-Neurophysin II-Copeptin and Aortic Arch Calcification on Mortality Risks in Hemodialysis Patients - Chang, Jia-Feng; Chou, Yu-Shao; Wu, Chang-Chin; Chen, Po-Cheng; Ko, Wen-Chin; Liou, Jian-Chiun; Hsieh, Chih-Yu; Lin, Wei-Ning; Wen, Li-Li; Chang, Shu-Wei; Tung, Tao-Hsin; Wang, Ting-Ming (Frontiers in Medicine, 2020)
Objective: Systemic hypoperfusion is intricately involved in neurohormone secretion, vascular calcification (VC) related impaired vasodilation, and luminal stenosis. We aimed to conduct a joint evaluation of vasopressin-neurophysin II-copeptin peptide (VP) and advanced aortic arch calcification (AAC) on all-cause and cardiovascular (CV) mortality in maintenance hemodialysis (MHD) patients. Methods: Unadjusted and adjusted hazard ratios (aHRs) of mortality risks were analyzed for different groups of VP and AAC in 167 MHD patients. The modification effect between higher VP and advanced AAC on mortality risk was examined using an interaction product term. Results: Interactions between VP and AAC with respect to all-cause and CV mortality were statistically significant. In multivariable analysis, higher VP predicted all-cause and CV mortality [aHR: 2.2 (95% confidence interval (CI): 1.1–4.5)] and 2.6 (95% CI: 1.1–4.6), respectively. Advanced AAC was associated with incremental risks of all-cause and CV mortality [aHR: 2.1 (95% CI: 1.1–4.0)and 2.5 (95% CI: 1.0–4.3), respectively]. Patients with combined higher VP (>101.5 ng/mL) and advanced AAC were at the greatest risk of all-cause and CV mortality [aHR: 4.7 (95% CI: 1.2–16.2)and 4.9 (95% CI: 1.1–18.9), respectively]. Conclusion: Combined VP and advanced AAC predict not only all-cause but also CV death in MHD patients, and a joint evaluation is more comprehensive than single marker. In light of hypoperfusion and ischemic events in vital organs, VP and AAC could act as more robust dual marker for prognostic assessment.